MBNL loss of function in smooth muscle as a model for myotonic dystrophy associated gastrointestinal dysmotility - Janel A. M. Peterson; Jesus A. Frias; Andrew N. Miller; Krishnakant G. Soni; Yi Zhang; Zheng Xia; John W. Day; Geoffrey A. Preidis; Thomas A. Cooper (Proceedings of the National Academy of Sciences, 2025)
Myotonic dystrophy type 1 (DM1) is the most common adult-onset muscular dystrophy and severely affects multiple organ systems, including the brain, heart, skeletal muscle, and gastrointestinal (GI) tract. Despite 80% of individuals with DM1 experiencing GI dysfunction that affects their daily life, the mechanisms of GI dysmotility in DM1 remain an understudied aspect of the disease. DM1 is caused by a CTG repeat expansion in the DMPK gene that, when expressed as an expanded CUG repeat RNA, sequesters and reduces the activity of the muscleblind-like (MBNL) RNA-binding protein family. We developed a mouse line with conditional, smooth muscle-specific knockout of Mbnl1 and Mbnl2 to model and investigate myogenic mechanisms contributing to GI dysmotility in DM1. Mice with Mbnl knockout exhibited delayed GI transit of small and large bowel in vivo and increased smooth muscle contractile tone of jejunum and colon segments ex vivo. Smooth muscle from the jejunum and colon showed no histopathology suggesting an intrinsic defect and contained increased phosphorylation of the 20 kDa myosin light chain (Mlc20), consistent with increased contraction. RNA sequencing of mouse and human DM1 GI samples enriched for smooth muscle revealed conserved misregulated alternative splicing of transcripts associated with the regulation of Mlc20 phosphorylation and smooth muscle contraction. These findings demonstrate that Mbnl knockout disrupts the regulation of contraction dynamics and causes GI smooth muscle hyperactivity, suggesting that therapeutics that reduce GI contractile activity may improve DM1 GI symptoms.